POLLINOSES IN CHILDREN AND ADOLESCENTS - I.I. Balabolkin; L.D. Ksenzova; E.V. Belyaeva (Педиатрическая фармакология)
The problem of pollinoses in children and adolescens are disacussed in the article on the basis of own investigations and the date of literature. The ussues of etiology, pathogenesis pollinoses, as clinic, diet therapy, pharmacotherapy are disacussed by authors in this work. It is shown, that allergen speacific immunotherapy posesses with high effectivenes in children and adolescents, suffering from pollen sensitization diseases.Key words: pollinoses, allergen specific immunotherapy, children, adolescens.